2011
DOI: 10.1007/s10903-011-9550-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Lifestyle Behavioral Change in Migrant South Asian Populations

Abstract: The purpose of this literature review is to describe and assess the cultural barriers to behavior change in migrant South Asians, given the high morbidity and mortality associated with cardiovascular disease in this population. We reviewed studies that explored the relationship between South Asian culture in the Diaspora and lifestyle behaviors. Our review produced 91 studies, of which 25 discussed the relationship between various aspects of South Asians’ belief system and their approach to modifying lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 56 publications
1
70
0
Order By: Relevance
“…A study amongst Filipinos in Australia identified a range of possible barriers including personal resources, cultural influences and environmental factors [40]. Amongst South Asians, gender roles, body image, cultural factors and knowledge seem to influence behavior change [41]. Further research is required to investigate the dietary and behavioral factors that are contributing to the upward trend in overweight, obesity and T2DM in migrant women in the UAE.…”
Section: Discussionmentioning
confidence: 99%
“…A study amongst Filipinos in Australia identified a range of possible barriers including personal resources, cultural influences and environmental factors [40]. Amongst South Asians, gender roles, body image, cultural factors and knowledge seem to influence behavior change [41]. Further research is required to investigate the dietary and behavioral factors that are contributing to the upward trend in overweight, obesity and T2DM in migrant women in the UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants, as immigrants and breadwinners, described their priorities being to support their families, not their health. For some, SA cultural priorities emphasize the importance of men spending most of their time providing for the family, leaving insufficient time for ‘leisure’ activities such as exercise [25]. While not uniquely SA (and none of the participants believed that being SA in and of itself increased CVD risk), this is a barrier that many SA men relate to [2527].…”
Section: Discussionmentioning
confidence: 99%
“…For some, SA cultural priorities emphasize the importance of men spending most of their time providing for the family, leaving insufficient time for ‘leisure’ activities such as exercise [25]. While not uniquely SA (and none of the participants believed that being SA in and of itself increased CVD risk), this is a barrier that many SA men relate to [2527]. Patel et al describe that pride is taken in a strong work ethic, and there is almost an expectation to forego health and exercise for work and family; especially among migrant SAs who have made significant sacrifices to secure better lives for their families, exercise for men is often viewed as taking time for oneself and seen as culturally inappropriate [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…These include gender roles, body image, physical activity misconception, and maintaining cultural identity [45]. Among Bhutanese households, while women are responsible for food preparation, the male and/or older females in the household exert a significant influence on the dietary decisions.…”
Section: Discussionmentioning
confidence: 99%